Exploring the Embodied Habitus of Early Career Social Workers. Issue 4 (2nd October 2022) - Stewart, Catherine; Fielding, Angela
ABSTRACT: This article explores experiences of social workers in their first year of practice working in the Australian health sector, revealing how unexpected challenges affected them. The information, collected through an Australia-wide online survey and self-selected interviews, was analysed thematically, and re-examined through Bourdieu's theory of social fields to reveal how expectations to "hit the ground running" were experienced within a landscape characterised by uncertainty of employment and lack of organisational support. These findings illuminate the complexity of meanings associated with starting out in the profession. The embodied habitus of these social workers revealed assumptions about needing to prove oneself, alongside needing to appear competent and to appear to be coping, which made support seeking difficult in some organisational cultures. IMPLICATIONS Exploring the embodiment of habitus for Australian early career social workers in the health sector provides opportunities to disrupt taken-for-granted assumptions about the first year of practice. The implications for improved support for early career social workers include enriching professional development and improving supervision support for these new front-line practitioners.